Wet Plume Removal Technologies for Coal-Fired Power Plants - Lin WANG; Guangjian LIU; Haiping CHEN (Zhongguo dianli)
The direct discharge of wet saturated flue gas after wet flue gas desulfurization in coal-fired power plants usually causes wet plume. In this paper, four wet plume elimination techniques, i.e., flue gas heating, flue gas condensation, flue gas condensation and reheating and membrane recovery of flue gas moisture, are analyzed theoretically, and the parameters in each technique are determined through quantitative calculation using the wet plume predication model. The results show: For reheating technology, if the ambient temperature is lower than 5 °C and the relative humidity is greater than 40%, the flue gas should be heated to above 100 °C; For condensation technology, if the ambient temperature is under 0 °C and the relative humidity of the environment is greater than 40%, flue gas temperature should be cooled down to below 15.5 °C; For condensation and reheating technology, the lower the condensation temperature, the lower reheating temperature should be. If the ambient temperature is higher than 5 °C and flue gas condensation temperature is cooled down to below 40 °C, the reheating temperature basically should not be higher than 80 °C; For membrane recovery technology, with the ambient temperature greater than 15°C and the water recovery rate higher than 40%, basically there will be negligible wet plume generated; If ambient temperature is lower than 5°C, the water recovery rate should be kept higher than 60%.